ECG Mishaps, Artifacts and Operator Faults - Mohammad Rasheed, Kaja (Bangladesh Critical Care Journal, 2017)
Electrocardiography is one of the most frequent bedside investigations in clinical practice. Often they are performed and interpreted by less experienced personnel with inadequate expertise.Equipment settings, proper technique and standardizations are prerequisites which may be overlooked, leading to costly and dangerous misinterpretations. This article highlights operational faults in ECG and emphasises that clinical staff must be equipped with necessary knowledge to identify these mistakes. It also tries to classify the common errors arising due to artifacts, electrode misplacement and improper standardization along with providing possible remedial measures. An awareness of these often neglected aspects and incorporating them in clinical discussions would not only enhance ECG interpretation but also improve patient safety. Bangladesh Crit Care J March 2017; 5(1): 63-67